Uji Aktivitas Ekstrak Etanol Daun Bandotan terhadap Penyembuhan Luka Sayat pada Tikus Putih Diabetes Melitus (Rattus norvegicus) - Tya Bella Arthamarisi Simbolon; Muhammad Yunus; Roy Indrianto Bangar (Lembaga Pengembangan Kinerja Dosen, 2025)
The wound healing process in individuals with diabetes mellitus is generally slower due to disruption of the inflammatory, proliferation, and regeneration mechanisms. Diabetics experience chronic metabolic disorders that impact immune cell function, blood circulation, and the regenerative capacity of fibroblasts and keratinocytes. Consequently, the wound healing process in diabetic patients is often more complex and takes longer. One approach to accelerating the wound healing process in this condition is the use of natural ingredients with anti-inflammatory, antimicrobial, and regenerative properties. One potential plant in this regard is the bandotan leaf (Ageratum conyzoides), which is known to contain active compounds such as flavonoids, alkaloids, and tannins that play a role in the wound healing process. This study was conducted to assess the effectiveness of bandotan leaf extract in accelerating wound healing in an animal model of diabetes mellitus. A total of 30 male white rats (Rattus norvegicus) that had been induced to become diabetic with streptozotocin were divided into six groups of five rats each. The groups included: a normal control group (healthy mice without diabetes), a negative control group (diabetic mice without treatment), a positive control group (given Metcovazin ointment as a standard), and three treatment groups that received topical application of bandotan leaf extract at graded concentrations of 10%, 15%, and 20%. A circular wound with a diameter of approximately 6 mm was made aseptically using a punch biopsy tool on the back of each mouse after being given ketamine anesthesia. Treatment was given daily for twelve consecutive days. The main parameters observed included daily measurements of the wound area to determine the rate of wound contraction.